2014
DOI: 10.1002/2014ja020203
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic lunar and solar daily variations during the last 100 years

Abstract: This paper describes long-term changes in the geomagnetic lunar (L) and solar (S) daily variations. We analyze the eastward component of the geomagnetic field observed at eight midlatitude stations during 1903-2012. The amplitude and phase for the semidiurnal component of the L and S variations are examined. Both L and S amplitudes correlate with the solar activity index F 10.7 , revealing a prominent 11 year solar cycle. In both cases, the correlation is slightly better with √ F 10.7 than F 10.7 . The sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 103 publications
3
26
0
1
Order By: Relevance
“…That is, the phase of these Fourier components shifts to later local times as solar activity increases. Yamazaki and Kosch (2014) also found a similar solar cycle effect on the phase of Sq variations. Olsen (1993) showed that the Sq current foci move to later local times during solar maximum, which is consistent with our results in Fig.…”
Section: Sq Focus Positionssupporting
confidence: 57%
See 1 more Smart Citation
“…That is, the phase of these Fourier components shifts to later local times as solar activity increases. Yamazaki and Kosch (2014) also found a similar solar cycle effect on the phase of Sq variations. Olsen (1993) showed that the Sq current foci move to later local times during solar maximum, which is consistent with our results in Fig.…”
Section: Sq Focus Positionssupporting
confidence: 57%
“…Butcher (1980) and Matsushita and Xu (1984) discussed that L currents flowing in the F region is improbable, and both L and Sq currents are likely to flow in the dynamo region. Yamazaki and Kosch (2014) evaluated the lunar semidiurnal variation using a slightly different method than previous authors. Instead of examining the luni-solar variation based on Chapman's phase law (Eq.…”
mentioning
confidence: 99%
“…According to numerical simulations, that pattern could be also due to a phase shift in the solar semidiurnal tide [e.g., Pedatella and Liu , ]. The presence of M 2 during SSWs has been also reported from other ground‐based observations as well as in situ observations on‐board satellites [e.g., Stening , ; Gasperini and Forbes , ; Lühr et al , ; Park et al , ; Yamazaki et al , ; Yamazaki , , ; Yamazaki and Kosch , ; Zhang et al , ]. Lunar tides in the ionosphere have been observed at other times, but their amplitudes are much smaller than at times of SSWs, i.e., northern hemispheric winter [e.g., Bartels , ; Chapman and Lindzen , ; Matsushita , ; Stening and Fejer , ; Stening and Rastogi , ; Pedatella and Forbes , ; Aveiro and Hysell , ; Eccles et al , ].…”
Section: Introductionmentioning
confidence: 73%
“…The Sq variations originate from electric currents flowing in the ionospheric dynamo region (80-160 km),where the electromotive force are driven by the neutral wind into the ionospheric wind dynamo system (e.g. Adebesin et al 2013a;Richmond and Maute 2014;Yamazaki and Kosch 2014). On the other hand, geomagnetic activities originate as a consequence of the interaction between the solar wind and the magnetosphere (e.g.…”
Section: Introductionmentioning
confidence: 99%